Analisis Pemilihan Supplier Kayu Pada Produk Furniture Menggunakan Metode Promethee - Silvia Firda Utami; Koko Hermanto; Iksan Adiasa; Tiya Indryani (Journal of Computer System and Informatics (JoSYC), 2022)
UD. Rahman Mebel is a company that produces various forms of furniture such as chairs, tables, cabinets, doors, windows, and various other forms of furniture. the purpose of this research is to determine the best supplier at UD. Rahman Mebel uses the Promethee Method. Four alternative suppliers have been determined by UD. Rahman Furniture namely: UD. Rini, UD. Dedi Putra, UD. Rangga Putra, UD Ujud Alam Riski and there were also four criteria tested, namely quality, price, service, and delivery. Based on the results of observations through interviews stated that the difficulties experienced in selecting the best supplier according to the company's criteria. For this reason, a solution to this problem is needed, namely by analyzing the determination of supplier choices using the Promethee method. From the results of this study is, the highest net flow value is UD. Rangga Putra is in first place with a score of 0.9999. The second rank is UD. Ujud Alam Riski with a score of 0.3333. The third rank is UD. Dedi Putra with a score of -0.9999. And the last rank is UD. Rini with a value of -0.3333.